Electron-accepting carborane viologen and iron based-supramolecular polymers for electrochromism and enhanced photocatalytic hydrogen evolution. Issue 46 (19th November 2020) - Yang, Xiaodong; Zhang, Yueyan; Zhang, Bingjie; Zhang, Sikun; Liu, Xu; Li, Guoping; Chu, Dake; Zhao, Yongtao; He, Gang
Abstract : CbV 2+ and its FeSPs with good optoelectronic properties were used to fabricate a high contrast ECD and enhanced visible-light-driven HER. Abstract : Highly electron-accepting viologen derivatives, o -carborane viologens (CbV 2+ ), and their iron based-supramolecular polymers (FeSPs) with tunable optoelectronic properties have been reported. Carborane viologens show excellent electron redox properties with low reduction threshold (−0.55 V) and three redox states (divalent cation, radical cation and neutral), which were used to fabricate high-performance electrochromic devices (ECDs). The enhanced photocatalytic hydrogen evolution of the CbV 2+ -based FeSP was achieved (105 times more than CbMV 2+, 2 times more than viologen-based FeSP) due to its multi-redox center, narrow band gaps, wide visible light absorption (∼580 nm), and especially the metal–ligand charge transfer (MLCT) process. This contribution provides important information for designing and understanding novel viologens and will greatly expand the scope of photocatalysis.